Alterations in myocardial stiffness in elite athletes assessed by a new Doppler index. Issue 10 (12th May 2008) - King, G J; Murphy, R T; Almuntaser, I; Bennett, K; Ho, E; Brown, A S
Abstract : Background: In elite athletes left ventricular (LV) morphological changes are predicted to alter passive pressure/volume characteristics by reducing myocardial stiffness and increasing compliance. Objective: To investigate the utility of a new Doppler tissue index based on the pressure volume relation ((E/Ea)/LVEDD), which provides a measure of myocardial stiffness, and to assess its usefulness in detecting cardiac adaptation in elite rowers. Methods: Thirty-six international rowers who had trained intensively and a control group of 30 sedentary subjects, matched for age and sex, were enrolled in the study. LV septal and posterior wall thickness, mass, chamber size, transmitral Doppler peak early (E) and late (A) diastolic filling velocities and isovolumic relaxation times were measured. Early diastolic myocardial velocities (Ea) were averaged from four sites at the mitral annulus; diastolic stiffness was assessed with the use of three indices E, Ea and the LV end-diastolic diameter in diastole (LVEDD). The ratio, (E/Ea)/LVEDD, provides a new index of diastolic stiffness. Rowers were further divided into two groups based on the presence or absence of left ventricular hypertrophy (LVH) ⩽12 mm and >12 mm. Results: No significant difference in Ea was found between the two groups, but there was a difference in the stiffness index, which remained after adjustment for body surface area and heart rate (controls 1.48 (0.3) vs athletes 1.17 (0.34), p = 0.016). No difference in stiffness index was found between the groups with LVH ⩽12 mm and >12 mm (1.11 (0.32) vs 1.17 (0.34), respectively, p = 0.68) Conclusions: Intense training reduces myocardial stiffness despite the development of LVH.